Clinicobiochemical profile in de novo multiple myeloma: A study from North India - Mir Sadaqat Hassan Zafar; Raiesa; Maqsood Ahmad Dar; Manzoor Ahmad Sofi (Asian Journal of Medical Sciences, 2023)
Background: Multiple myeloma (MM) is the second most common hematological malignancy after non-Hodgkin lymphoma. The clinical spectrum varies from asymptomatic forms to manifestations of anemia, bone pains, and eventually spontaneous fractures, renal failure, and frequent infections. Aims and Objectives: The aims and objectives of the study are to assess the clinical and biochemical parameters in newly diagnosed cases of MM. Materials and Methods: This study was conducted in the Department of Clinical Hematology of a tertiary care hospital of North India. It was a prospective observational study over a period of 2-year duration. A total of 50 newly diagnosed patients of MM were enrolled and analyzed for clinical data. Results: Out of 50 MM patients, 68% were males and 32% were females. Mean±SD of age was 62.48±8.140 years. Forty patients (80%) had anemia (isolated anemia 4 patients), 22 patients had renal failure (44%), 20 patients (40%) had spontaneous fractures (isolated pathological fracture 6 patients), and 14 patients (28%) had bone pains (isolated bone pains 4 patients). Mean±SD of hemoglobin before the start of treatment was 8.69±2.85 g/dL. Twenty-six patients (52%) had associated comorbidity mainly hypertension (32%) and diabetes mellitus (8%), while 48% of patients had no history of previous comorbid illness. Immunoglobulin (Ig)G-λ type MM were 16 cases (32%), IgA-λ type were 6 cases (12%), IgG-κ were 10 cases (20%), IgA- κ were 4 cases (8%), Kappa type were 10 cases (20%), and biclonal 2 cases (4%). Twelve patients (24%) were in the International Staging System (ISS), 22 patients (44%) in ISS-II, and 16 patients (32%) in ISS-III disease stage. Conclusion: Treating physician should have a high index of suspicion for this disorder once elderly patients present with anemia, especially in combination with renal dysfunction and/spontaneous fractures for early diagnosis and treatment.